2001
DOI: 10.1016/s0277-5387(01)00869-5
|View full text |Cite
|
Sign up to set email alerts
|

Mixtures obtained by reacting trans-(±)-1,2-diaminocyclohexane with acetylacetone in the presence of simple cobalt(II) salts

Abstract: In the absence of a metal ion, racemic trans-1,2-diaminocyclohexane (trans-(9 )DCH) reacts with acetylacetone (acacH) (1:2.5 mole ratio) to form the bisoxoenamine condensation product, boe (1). (9) co-crystallise. Complexes 1, 5, 7, 8 and 9 were characterised using X-ray crystallography. The major difference between using CoCl 2 ·6H 2 O and Co(ClO 4 ) 2 ·6H 2 O in reactions involving ( 9)DCH and acacH is that no DCH/acacH condensation products are identified in the product mixtures when the perchlorate salt i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Compound 1 was comprehensively characterized by NMR spectroscopy, IR spectroscopy as well as elemental analysis. 1 H NMR spectrum of 1 reveals the methine proton of the ketoiminate backbone at δ = 5.20 ppm, which is consistent with analogous bridged bis(β‐ketimine) ligand linked by 4,4′‐methylene‐bis(2–6‐diisopropylaniline),6b and diaminocyclohexane 6a,6c…”
Section: Resultssupporting
confidence: 63%
“…Compound 1 was comprehensively characterized by NMR spectroscopy, IR spectroscopy as well as elemental analysis. 1 H NMR spectrum of 1 reveals the methine proton of the ketoiminate backbone at δ = 5.20 ppm, which is consistent with analogous bridged bis(β‐ketimine) ligand linked by 4,4′‐methylene‐bis(2–6‐diisopropylaniline),6b and diaminocyclohexane 6a,6c…”
Section: Resultssupporting
confidence: 63%
“…X-ray structural analysis revealed that 3 is a 1D coordination polymer (see Fig. 4), crystallized in the monoclinic space group C2/c, and straddles the (11), O(3)À Ag(1)/Ag(1A) 80.35 (10). Symmetry code: a) Àx þ 1, Ày þ 1, Àz þ 2; b) Àx þ 3 / 2 , Ày, z.…”
Section: Resultsmentioning
confidence: 99%
“…The ligand N,N 0 -bis(acetylacetone)-1R,2R-diaminocyclohexane (L) was synthesized according to the literature procedure [10]. NMR spectra were recorded on a Bruker ALX 300 spectrometer operating at 300 MHz for 1 H. Chemical shifts (d, ppm) were reported with reference to SiMe 4 ( 1 H).…”
Section: Generalmentioning
confidence: 99%
See 2 more Smart Citations